Pengaruh E-Service Quality, Online Promotion dan Persepsi Harga terhadap Loyalitas Pelanggan pada Pengguna Aplikasi Indrive di Surabaya - Ririn Sasmianingtias; Lia Nirawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of e-service quality, online promotion and price perception on customer loyalty among InDrive application users in Surabaya. Type of quantitative research with multiple linear regression. The population in this research is the people of Surabaya who have used the InDrive service and in the sampling process used a purposive sampling technique with a total of 100 respondents who had been determined from the Solvin formula calculation. The results of this research are that it is proven that there is an influence of the three independent variables on customer loyalty simultaneously (F test) as seen from the tcount value which is greater than ttable or 15.044 > 2.70 with a significance level of 0.000 < 0.05. There is a partial or individual influence on e-service quality, online promotions and price perceptions on customer loyalty. This is proven by the calculated tcount value of each independent variable, namely e-service quality (X1) of 3.032; online promotion (X2) 2,252; and price perception (X3) 2.084 is greater than the ttable value, namely 1.985. And the significance value is smaller than 0.05, namely 0.003; 0.027; and 0.040.